Reducing respondents' perceptions of bias in survey research. Issue 3 (October 2021) - Mayer, Adam
Response rates for surveys have declined steadily over the last few decades. During this period, trust in science has also waned and conspiratorial theorizing around scientific issues has seemingly become more prevalent. In our prior work, we found that a significant portion of respondents will claim that a given survey is "biased." In this follow-up research, we qualify these perceptions of bias and point to potential causes and ameliorative mechanisms.